Optimizing Educator and Student Readiness in the Digital Transformation of Islamic Religious Education: Integrating Responsible AI Use, Religious Moderation, Plagiarism Risk Mitigation, Academic Integrity, and Data Literacy in Inclusive Islamic Education - Romadhon Romadhon; Masykur Amin; Syahruddin Mahmud (Indo Green Journal, 2026)
The rapid development of artificial intelligence has significantly influenced educational practices, including Islamic Religious Education (PAI). AI offers opportunities to support personalized learning, expand access to Islamic learning resources, provide feedback, and create more inclusive learning environments. However, its use also raises ethical and pedagogical challenges, particularly related to educator and student readiness, plagiarism risks, academic integrity, data literacy, and the preservation of religious moderation values. This study aims to analyze strategies for optimizing educator and student readiness for the digital transformation of Islamic Religious Education by integrating responsible AI use, plagiarism mitigation, academic integrity, data literacy, and religious moderation in inclusive PAI learning. This research uses a library research method with a qualitative-descriptive approach by reviewing relevant scholarly literature published within the last five years. The findings show that AI readiness should not be limited to technical competence, but must also include ethical awareness, critical thinking, digital tabayyun, and the ability to evaluate AI-generated information. Educators play a strategic role in guiding students to use AI transparently, responsibly, and in accordance with Islamic values such as honesty, amanah, justice, and responsibility. The study also highlights the importance of redesigning assessment methods, strengthening data literacy, and integrating religious moderation to prevent misinformation, intolerance, and academic misconduct. This study concludes that responsible AI integration can strengthen Islamic Religious Education when supported by ethical guidance, inclusive pedagogy, and strong academic integrity. Therefore, AI should be positioned as a supportive learning tool that enhances, rather than replaces, educators' moral and spiritual roles in PAI learning